Barriers to Inclusion: Challenges Faced by Physically Impaired Students in Higher Education Institutions of Bahawalpur, Pakistan - Mohsin, Muhammad Rameez; Rizwan ul Haq Aamir; Salman Khan (Sociological Research And Innovation, 2024)
This research is directed at supporting and ensuring equal access to higher education services for physically impaired individuals and mitigating the gap between the acquisition of higher education and disability. For this purpose, it examines the difficulties encountered by physically disabled students in Bahawalpur's higher education institutes (HEIs), concentrating on the institutional obstacles that restrict their social and academic integration. The cluster sampling method was utilized in this study. A total of 100 respondents from the Islamia University of Bahawalpur studying at the B.S. level were chosen. For a better understanding of the subject matter, six themes were developed including the experiences of isolation and loneliness and the experiences of discrimination and discriminatory behavior. The absence of suitable study materials, poor physical accessibility, and a lack of knowledge among stakeholders about the rights of students with impairments were identified as the main problems. Accessible restrooms and ramps are basic facilities that many universities lack, while educational materials in Braille and audiobook formats are frequently out of stock. The findings emphasize how social marginalization has an emotional and psychological effect on students, making them feel more stressed and alone. Steps to improve the situation include mandatory training for teachers and staff to raise awareness about disability rights, strengthening the physical infrastructure for accessibility, and ensuring the availability of accessible academic materials.